Mitochondrial protein enriched extracellular vesicles discovered in human melanoma tissues can be detected in patient plasma. Issue 1 (1st December 2019) - Jang, Su Chul; Crescitelli, Rossella; Cvjetkovic, Aleksander; Belgrano, Valerio; Olofsson Bagge, Roger; Sundfeldt, Karin; Ochiya, Takahiro; Kalluri, Raghu; Lötvall, Jan
ABSTRACT: Extracellular vesicles (EVs), including exosomes and microvesicles, are secreted from all cells, and convey messages between cells in health and disease. However, the diversity of EV subpopulations is only beginning to be explored. Since EVs have been implicated in tumour microenvironmental communication, we started to determine the diversity of EVs specifically in this tissue. To do this, we isolated EVs directly from patient melanoma metastatic tissues. Using EV membrane isolation and mass spectrometry analysis, we discovered enrichment of mitochondrial membrane proteins in the melanoma tissue-derived EVs, compared to non-melanoma-derived EVs. Interestingly, two mitochondrial inner membrane proteins MT-CO2 (encoded by the mitochondrial genome) and COX6c (encoded by the nuclear genome) were highly prevalent in the plasma of melanoma patients, as well as in ovarian and breast cancer patients. Furthermore, this subpopulation of EVs contains active mitochondrial enzymes. In summary, tumour tissues are enriched in EVs with mitochondrial membrane proteins and these mitochondrial membrane proteins can be detected in plasma and are increased in melanoma, ovarian cancer as well as breast cancer.